The public relations writer's handbook : - Aronson, Merry (Jossey-Bass, 2007)
The second edition of The Public Relation's Writer's Handbook offers a simple, step-by-step approach to creating a wide range of writing, from basic news releases, pitch letters, biographies, and media alerts, to more complex and sophisticated speeches, media campaign proposals, crisis responses, and in-house publications. In addition, the thoroughly expanded and updated second edition shows how to keep up with the best practices of the public relations profession, as well as with the speed made possible and required by the digital age.